Exploring new facets of interleukin-7 receptor-mediated signaling in T-cell leukemia - Ramalho, Ana Sofia Navarro (2022)
Tese de mestrado, Oncobiologia, Universidade de Lisboa, Faculdade de Medicina, 2019